Perceptions of influenza and SARS-CoV-2 vaccination among health care personnel in Thailand, 2024 - Kriengkrai Prasert; Prabda Praphasiri; Darunee Ditsungnoen; Sribud Srichaijaroonpong; Ratchadaporn Ungcharoen; Anusak Kerdsin; Sutthichai Nakphook; William W. Davis; Chakrarat Pittayawonganon; Eva S. Bazant; Ann C. Moen; Jaymin C. Patel; et al. (PLoS ONE, 2025)
Background Influenza and COVID-19 vaccinations are recommended for health care personnel (HCP) in Thailand, but uptake depends on HCP perceptions and motivations. Methods To assess factors associated with self-reported influenza vaccination in the most recent season and intention to receive future COVID-19 vaccination annually, HCP from 16 hospitals across eight Thailand provinces were surveyed during December 2023 through January 2024. Additional survey variables included demographic and occupational characteristics, prior experiences with vaccination, perceptions of disease severity and vaccine safety and effectiveness. Multilevel mixed effect multivariable logistic regression was used, accounting for variability at provincial and hospital levels. Results Overall, 2,180 HCP were surveyed. Three-quarters (74.8%) reported influenza vaccination in the most recent season, and 58.1% intended to receive COVID-19 vaccination annually in the future. Previous influenza vaccination was strongly associated with reported vaccination in the current season (adjusted odds ratio [aOR] 2.94, 95% confidence interval [CI] 2.68–3.23). For future COVID-19 vaccination, perceived vaccine safety was strongly associated (aOR 3.49, 95% CI 3.18–3.84). Perceived disease severity was higher for COVID-19 than for influenza, but perceived vaccine safety and effectiveness were higher for influenza than for COVID-19. The most common barrier to influenza vaccination was insufficient time to get vaccinated (23.7%); whereas the most common barrier for COVID-19 vaccination was vaccine safety concern (30.0%). Conclusions Improving vaccination coverage among HCP might need different approaches for influenza and COVID-19 vaccines. Improving convenience might be especially important for increasing influenza vaccination coverage, whereas providing reassurance about COVID-19 vaccine safety might be especially important for COVID-19.